Improving staff retention with learning opportunities. (2nd February 2019) - Ashurst, Adrian
Abstract : Continuous professional development is key for all heatlh professionals. But nurses are often pressed for time and work irregular hours, here e-learning can help. Adrian Ashurst highlights the ways staff can be supported with learning.